Corrosion Behavior of Anodic Self-Ordered Porous Oxide Layers on Stainless Steel - Prado, Lucia; Anastasiou, Evangelia; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2021)
In the present study we performed anodization of stainless steel AISI 316L varying the voltage, time and H2O concentration in the electrolyte obtaining self-ordered porous oxides. Open-circuit potential measurements, potentiodynamic polarization and electrochemical impedance spectroscopy were performed in 0.1 M H2SO4, 0.1 M NaCl and 0.1 M NaOH electrolytes. The metallic substrate underneath the grown oxide was also characterized. The results indicate that the corrosion behavior of the metallic substrate is not impaired by the anodization treatments. However, "crevice-induced intergranular corrosion" between the oxide and the metallic substrate was revealed after electrochemical measurements in the acidic electrolyte.
CRIS-Team WoS Importer:2021-03-05